Sistem Pendukung Keputusan Pemilihan Indekost Pemuda Dengan Menggunakan Metode Simple Additive Weighting (Saw) - Siregar, Gunayanti Kemalasari; Susanto, Lilik Joko (Jurnal Ilmiah Sistem Informasi (JISI), 2022)
Housing development for youth is currently the main priority because boarding houses are considered ideal and practical places to choose a place to live. The number of enthusiasts who choose boarding houses for housing is due to many considerations, including cost, facilities, and strategic location. Due to these considerations, many young boarding houses choose suitable temporary housing. A Decision Support System (DSS) is a technique that can solve a problem in semi-systematic and non-systematic terms. This decision support system will later be made using the Simple Additive Weighting (SAW) method with the hope of solving the problems experienced by students. The author's research steps are determining criteria and alternatives, collecting data from questionnaires distributed to students, carrying out calculations, and ranking alternatives. From the calculation results, it is obtained that Kost2 is the best alternative.